Stratigraphic relationships of the Eocene Duchesne River Formation and Oligocene Bishop Conglomerate, northeastern Utah—pulsed sedimentary response to rollback of the subducted Farallon slab (Geology of the Intermountain West, 2022)
The Uinta Mountains are an east-west-trending, reverse fault-bounded, basement-cored Laramide uplift. The Eocene Duchesne River Formation and Oligocene Bishop Conglomerate represent late stage, intermontane basin fill of the Uinta Basin in northeastern Utah. Detailed mapping (1:24,000 scale), clast counts in conglomerate beds, description of lithology and stratigraphic contacts, and radiometric dating of pyroclastic fall beds of the Duchesne River Formation and Bishop Conglomerate in the Vernal NW quadrangle in northeastern Utah reveal stratal geometries of middle Cenozoic depositional units, the uplift and unroofing history of the eastern Uinta Mountains, and give evidence for the pulsed termination of Laramide uplift related to rollback of the Farallon slab and lithospheric delamination. These relationships show the continuation of Laramide uplift in this region until after 37.9 Ma and before 34 Ma, an age younger than the previously reported 45 to 40 Ma. The Duchesne River Formation consists of four members: the Brennan Basin, Dry Gulch Creek, Lapoint, and the Starr Flat. A normal unroofing signal is found within the formation with a downward increase in Paleozoic clasts and an upward increase in Proterozoic clasts. The oldest member, the Brennan Basin Member contains 80% to 90% Paleozoic clasts and less than 20% Proterozoic clasts. Conglomerate beds in the progressively younger Dry Gulch Creek, Lapoint, and Starr Flat Members of the Duchesne River Formation show significant increases in Proterozoic clasts (34% to 73%) and a decrease in Paleozoic clasts (27% to 66%). The Bishop Conglomerate overlies the Duchesne River Formation, but shows no clear change in clast composition. In the Duchesne River Formation, the proportion of beds containing fine gravel to boulder-sized clasts decreases significantly with distance from the Uinta uplift, from almost 100% near the source (